Avian turnover at Harvard Forest, Massachusetts, USA, 1948-2016 - Daniel S. Cooper; Daniel S. Cooper (Frontiers in Ecology and Evolution)
Multi-decadal datasets from systematic surveys of birds are rarely published, despite their potential to yield important information about local changes in the environment over time. I compare bird surveys at Harvard Forest in central Massachusetts, USA, between 1993 and 2016 with two unpublished annotated bird checklists from the area (1948 and 1970), along with data from other long-term bird survey sites in New England, and regional community science data. While a handful of breeding species at the Harvard Forest are common each year, species turnover has been constant, with roughly a third of bird species found one survey year and not the other. I list 18 species that have apparently colonized Harvard Forest as breeding species after 1948, and 16 that have declined since then, including two to the point of extirpation. I also note several examples of phylogenetic replacements in the recent vs. historical avifauna. More colonizing species than declining species are at their northern range limit rather than their southern limit in southern New England, and more migratory species appear to be declining than colonizing. More colonizing species favor forest interior than declining ones, and nearly all declining species are associated with edge/early-successional habitats or are considered habitat generalists. The majority of species to have colonized Harvard Forest since 1948 show positive statewide population trends, and none showed a loss in the number of breeding bird atlas blocks occupied between the 1970s and the 2000s. I identify three declining or extirpated species, Ruffed Grouse, Eastern Whip-poor-will, and Olive-sided Flycatcher, as particularly deserving of conservation attention. Long-term, site-scale monitoring is essential to detect the impact of local forest management techniques, which at Harvard Forest has included the creation of experimental clear-cuts, the loss of conifer plantations, and the continued maturation of the mixed hardwood forest.